Social devaluation of African Americans and race‐related conspiracy theories. (30th September 2018) - Davis, James; Wetherell, Geoffrey; Henry, P.J.
Abstract: African Americans in the United States endorse conspiracy theories at greater rates than Whites. The extant literature explains this pattern in terms of a rational motivation to blame the social system for prejudice and discrimination. However, little research distinguishes between race‐relevant conspiracy theories against African Americans and general conspiracy theories. We propose that African Americans may seek out race‐relevant conspiracy theories in particular because they satisfy a search for meaning that is brought about by chronic social devaluation. We present two studies that examine this social devaluation hypothesis. In Study 1 African Americans endorsed race‐relevant conspiracy theories, even when controlling for perceptions of discrimination, an aspect of system blame. Study 2 employed an experimental affirmation of social value that significantly reduced African Americans' endorsement of race‐relevant conspiracy theories consistent with the social devaluation hypothesis. These data indicate that there may be psychologically adaptive features of race‐relevant conspiracy theory endorsement.